EFL LEARNING ACTIVITIES IN INCLUSIVE CLASSES IN JUNIOR SECONDARY SCHOOLS - Murni, S.N.W. (Universitas Pendidikan Ganesha, 2019)
In the development of education, nowadays Indonesia has been developing an inclusive education system to eliminate discrimination between children with special needs and the society. This research objective was to evaluate the implementations of EFL teachers’ learning activities in inclusive classes in the Junior Secondary School, Denpasar District, Bali. The research design implemented was that of observational study which used an observation sheet to collect data. The data of the research was analysed qualitatively. The findings show that the learning activities conducted by teachers covered the needs of regular students, however, the learning approach/method/strategies provided by both teachers did not consider the characteristics of slow learning and attention deficit students. The used of Inquiry Based Learning was not appropriate to be applied for either slow learning and attention deficit students. As seeing the characteristics of both special needs students, teachers are expected to modify their teaching method/strategies. Besides, the teaching media and sources need be adaptive as well.